1986
DOI: 10.1136/thx.41.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical lung shunting in pulmonary fibrosis.

Abstract: Eleven patients with cryptogenic fibrosing alveolitis were evaluated for the presence of pulmonary shunting by injection of radiolabelled particles of macroaggregated albumin larger than lO 4um in diameter and by body scanning with a gamma camera. The mean shunt of 9% (SD 2%) in the patients was not significantly different from the mean shunt of 7% (2%) measured in 10 normal controls. These findings suggest that shunting is not an important part of the gas exchange abnormalities noted in such patients.Arteriov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Inflammatory and hypoxic stimuli originating from the fibrotic intima may have stimulated angiogenic sprouting of ACKR1 + venous ECs from the outer arterial layer into the media. Vascular malformations involving arteries and veins, such as arteriovenous shunts, have been previously described in IPF lungs (79, 80), however, the endothelial origin and the mechanisms implicated in these vascular aberrations have remained largely unexplored. Altogether, our findings demonstrated that vascular endothelial turnover is compromised in IPF lungs favoring the expansion of venous ECs while restricting that of alveolar capillaries.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory and hypoxic stimuli originating from the fibrotic intima may have stimulated angiogenic sprouting of ACKR1 + venous ECs from the outer arterial layer into the media. Vascular malformations involving arteries and veins, such as arteriovenous shunts, have been previously described in IPF lungs (79, 80), however, the endothelial origin and the mechanisms implicated in these vascular aberrations have remained largely unexplored. Altogether, our findings demonstrated that vascular endothelial turnover is compromised in IPF lungs favoring the expansion of venous ECs while restricting that of alveolar capillaries.…”
Section: Resultsmentioning
confidence: 99%
“…A third possible mechanism relates to pleuroparenchymal and/or bronchial-pulmonary artery anastomoses described histopathologically in patients with fibrosing lung disease [30]. While the clinical importance of shunting within the lungs is yet to be established [31], the development of shunts could theoretically increase the PVV as fibrosis progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Jacob et al [10] postulated that increased PVV in IPF patients can be related to the following reasons : i) Diversion of the blood flow from fibrotic areas to relatively spared lung regions, resulting in dilation of vessels and therefore an increased PVV, ii) Increased negative pressure during inspiration, due to increased lung stiffness in IPF patients, that result in the dilation effect on blood vessels, iii) Increased pleuro-parenchymal and bronchial-pulmonary arterial anastomosis that was previously described in histological lung specimens of IPF patients [23,24].…”
Section: Discussionmentioning
confidence: 96%